2017
DOI: 10.3389/fpls.2017.02193
|View full text |Cite
|
Sign up to set email alerts
|

Application of Endophytic Pseudomonas fluorescens and a Bacterial Consortium to Brassica napus Can Increase Plant Height and Biomass under Greenhouse and Field Conditions

Abstract: Plant associated bacteria with plant growth promotion (PGP) properties have been proposed for use as environmentally friendly biofertilizers for sustainable agriculture; however, analysis of their efficacy in the field is often limited. In this study, greenhouse and field trials were carried out using individual endophytic Pseudomonas fluorescens strains, the well characterized rhizospheric P. fluorescens F113 and an endophytic microbial consortium of 10 different strains. These bacteria had been previously ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 56 publications
2
47
1
Order By: Relevance
“…In recent years, a large deal of literature has been produced on co‐inoculation (consortium) of agriculturally beneficial microorganisms and in many cases benefits have been observed compared with the single inoculation (Akintokun and Taiwo, ; Sahu et al ., ; Molina‐Romero et al ., ; Lally et al ., ; Orozco‐Mosqueda et al ., ; Sahu et al ., ). The present study shows that the beneficial endophytes E. cloacae RCA25 and H. huttiense RCA24 can be promising strains to improve, directly or indirectly, nitrogen fixation in rice plants under greenhouse conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a large deal of literature has been produced on co‐inoculation (consortium) of agriculturally beneficial microorganisms and in many cases benefits have been observed compared with the single inoculation (Akintokun and Taiwo, ; Sahu et al ., ; Molina‐Romero et al ., ; Lally et al ., ; Orozco‐Mosqueda et al ., ; Sahu et al ., ). The present study shows that the beneficial endophytes E. cloacae RCA25 and H. huttiense RCA24 can be promising strains to improve, directly or indirectly, nitrogen fixation in rice plants under greenhouse conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It produces a soluble green pigment, pyoverdine responsible for its fluorescence. The microbe has the ability to grow in diverse environments, utilizes a wide range of carbon sources, tolerates disparate temperatures and proliferates in pH ranging from 4 to 8 [18][19][20]. These characteristics have been tailored naturally in order to render P. fluorescens suitable for bioremediation, in pathogen control and as biofertilizers.…”
Section: Metabolic Malleability Of P Fluorescensmentioning
confidence: 99%
“…For instance, Camacho et al [119] showed that a Bacillus strain, considered a proper PGPR, was beneficial in the R. tropici-Phaseolus vulgaris symbiosis, but had deleterious effects when interacting with the B. japonicum-Glycine max relationship. Table 1 also shows some other examples in which the effects on plant growth and yield derived from inoculation of PPB consortia in field tests were not always beneficial or did not produce significant increases of yield or quality [87,88,[110][111][112][113][114][115]. These negative findings might be due to the enormous variety of factors affecting crops, especially in the field, where microbiomes and plants are subjected to biotic and abiotic stresses.…”
Section: Better Together-inoculation With Ppb Consortia Vs Individuamentioning
confidence: 99%